FeCe / SiO2 composite aerogel catalytic material as well as preparation method and application thereof

The microwave hydrothermal method of FeCe/SiO2 composite aerogel catalytic material is prepared by solving the problem of low efficiency of removing NO and CO in coal-fired flue gas, achieving efficient catalysis and stability, suitable for large-scale industrial production, and has good high-temperature and high-pressure performance.

CN119236953AInactive Publication Date: 2025-01-03INNER MONGOLIA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411357387.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing catalysts have low efficiency and high cost to remove NO and CO in coal-fired flue gas, and have problems with narrow temperature windows and by-product N2O, which limits the further development of the technology.

Method used

The FeCe/SiO2 composite aerogel catalytic material was prepared by microwave hydrothermal method, and SiO2 aerogel was used as a support to support Fe and Ce oxides to improve catalytic activity and stability, and achieve efficient catalytic conversion of CO and NO.

Benefits of technology

It achieves high specific surface area and dispersion, improves catalytic activity and stability, is suitable for large-scale industrial production, has good oxygen storage capacity and cerium/ferrous ion coupled variable valence characteristics, can efficiently catalyze the conversion of CO and NO into harmless gas, and is suitable for high-temperature and high-pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236953A_ABST
    Figure CN119236953A_ABST
Patent Text Reader

Abstract

The invention provides a FeCe / SiO2 composite aerogel catalytic material as well as a preparation method and application thereof, and belongs to the technical field of flue gas denitration catalytic materials. According to the FeCe / SiO2 composite aerogel catalytic material, SiO2 aerogel is used as a carrier, and a transition metal oxide is loaded on the carrier; the transition metal oxide is an oxide of Fe and an oxide of Ce. The preparation method comprises the following steps: dissolving cerium salt and iron salt in water, then adding SiO2 aerogel, uniformly mixing, and carrying out microwave hydrothermal synthesis reaction on the obtained mixed solution to obtain a precursor material; and roasting the precursor material to obtain the FeCe / SiO2 composite aerogel catalytic material. The FeCe / SiO2 composite aerogel catalytic material provided by the invention has the characteristics of uniform pore size distribution, high specific surface area, large pore volume and strong adsorption capacity, and can efficiently catalyze NO and CO to be converted into N2 and CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flue gas denitration catalytic materials, and in particular to a FeCe / SiO 2 Composite aerogel catalytic material and its preparation method and application. Background Art

[0002] NO not only pollutes the atmosphere, but also harms human health. NO will bind to hemoglobin in the human body, thus affecting the ability of hemoglobin to transport oxygen. At the same time, NO can be oxidized in the air to generate NO 2 , NO 2 It is one of the main causes of photochemical smog and acid rain. How to remove NO from industrial waste gas has become a global hot topic. The most practical application now is the selective catalytic reduction of ammonia (NH 3 -SCR), but commonly used industrial catalysts such as V 2 O 5 -WO 3 / TiO 2 There are high operating temperatures, narrow temperature windows (300-400°C), and a large amount of N 2 The disadvantages of the technology, such as the production of byproducts such as NO, limit the further development of the technology. In addition to NO, CO also exists in industrial waste gases such as sintering flue gas and automobile exhaust. Therefore, using CO as a reducing agent can remove these two harmful gases at the same time, achieving the effect of killing two birds with one stone.

[0003] At present, researchers have developed many denitrification catalysts for catalyzing the reduction of NO with CO. Common CO reduction catalysts are divided into two types: precious metal catalysts and non-precious metal catalysts. Although precious metal catalysts have high denitrification efficiency, their high cost and high temperature deactivation disadvantages limit their application range. Rare earth elements play an irreplaceable role in many fields of the national economy. CeO 2 As an extremely important rare earth oxide, CeO is widely used in many fields. 2 It has a large specific surface area and excellent oxygen storage performance, and can store and release more active oxygen. 2 O 3 The extremely high lattice oxygen storage capacity makes it an important oxygen carrier material in the fields of chemical looping combustion and chemical oxygen storage. However, both types of oxides have essential defects, such as CeO 2 The thermal stability is poor, and the single Fe 2 O 3 It is slightly inert, which makes it difficult to be directly applied in the field of catalysis. Summary of the invention

[0004] In order to solve the above-mentioned coal-fired flue gas catalytic denitrification technical problem, the present invention proposes a FeCe / SiO 2 Composite aerogel catalytic material and preparation method and application thereof, the present invention synthesizes FeCe / SiO 2 Aerogel provides rich porosity and specific surface area, and develops FeCe / SiO with high specific surface area, high dispersibility and high deep catalytic oxidation ability. 2 Composite oxide aerogel catalytic materials.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a FeCe / SiO 2 Composite aerogel catalytic material, based on SiO 2 The aerogel is a carrier, and the carrier is loaded with transition metal oxides; the transition metal oxides are Fe oxides and Ce oxides.

[0007] The second technical solution of the present invention is a FeCe / SiO 2 The preparation method of the composite aerogel catalytic material comprises the following steps:

[0008] Dissolve cerium salt and iron salt in water, then add SiO 2 aerogel, after being uniformly mixed, subjecting the obtained mixed solution to a microwave hydrothermal synthesis reaction to obtain a precursor material;

[0009] Calcine the precursor material to obtain the FeCe / SiO 2 Composite aerogel catalytic materials.

[0010] The third technical solution of the present invention is a FeCe / SiO 2 Application of composite aerogel catalytic materials in catalysis of flue gas containing CO and NO.

[0011] The fourth technical solution of the present invention is a flue gas denitration catalyst, the raw materials of which include the above-mentioned FeCe / SiO 2 Composite aerogel catalytic materials.

[0012] The present invention discloses the following technical effects:

[0013] The present invention adopts microwave hydrothermal method to prepare FeCe / SiO 2 The composite aerogel catalytic material can obtain uniformly dispersed nanoparticles, increase the specific surface area and dispersion of the catalytic material, and further increase the catalytic activity and stability. In addition, the preparation method of the present invention is simple, low-cost, and suitable for large-scale industrial production.

[0014] The FeCe / SiO prepared by microwave hydrothermal method2 Composite aerogel catalytic materials have the characteristics of uniform pore size distribution, high specific surface area, large pore volume and strong adsorption capacity.

[0015] The present invention adopts microwave hydrothermal method to prepare FeCe / SiO 2 Composite aerogel catalytic materials can ensure the yield and purity of products, are cheap and readily available, are non-flammable to avoid flammability and explosion, are non-toxic, and have low critical temperature and pressure, so the requirements for equipment are not too harsh.

[0016] The FeCe / SiO 2 The composite aerogel catalytic material has a high oxygen storage capacity and cerium / iron ion coupling valence change characteristics, and can efficiently catalyze the conversion of CO and NO into non-toxic and harmless CO 2 and N 2 , and has good application prospects in the field of catalysis involving oxygen storage / release and redox cycle processes.

[0017] The present invention also provides the FeCe / SiO 2 The application of composite aerogel catalytic materials is suitable for a variety of chemical reactions. Experiments have shown that FeCe / SiO 2 Composite aerogel catalytic materials have high catalytic activity and stability, and can maintain good catalytic effects under harsh conditions such as high temperature and high pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The FeCe / SiO 2 Flow chart of the preparation of composite aerogel catalytic materials.

[0020] Figure 2 FeCe / SiO obtained in Example 1-9 2 The conversion rate of NO by composite aerogel catalytic material;

[0021] Figure 3 FeCe / SiO obtained in Example 1-9 2 Graph showing the conversion rate of CO by composite aerogel catalytic materials. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] The present invention provides a FeCe / SiO 2 Composite aerogel catalytic material, based on SiO 2 The aerogel is a carrier, and the carrier is loaded with transition metal oxides; the transition metal oxides are Fe oxides and Ce oxides.

[0028] In some embodiments of the present invention, the Ce loading on the carrier is 10 wt %, wherein the molar ratio of Ce:Fe is 10:(1-3).

[0029] The present invention selects cerium (Ce) and iron (Fe) as catalyst components and utilizes the synergistic effect between different components to purify coal-fired flue gas. FeCe / SiO 2 Composite aerogel catalytic material. The present invention utilizes SiO 2The high porosity and abundant acidic sites of aerogel can promote the rapid adsorption and decomposition of substrate molecules, exerting a catalytic effect. The catalytic material can oxidize CO and NO to N 2 , CO 2 . In addition, the present invention provides a different preparation method for aerogel catalytic materials compared to the prior art. Due to the different preparation methods, the aerogel structures formed are also different, which in turn affects the catalytic performance of the final catalytic material. In addition, the present invention uses the prepared silica aerogel as a carrier, omits the supercritical drying of carbon dioxide in the preparation process, and the steps are simple and easy to operate, and can be used for large-scale industrial production.

[0030] In some embodiments of the present invention, the molar ratio of the Ce element in the Ce oxide to the Fe element in the Fe oxide is 10:(1-3).

[0031] In the present invention, when the iron content is too little, the active sites will be reduced, and iron can promote the redox cycle of cerium in the catalyst. If the iron content is too little, the activity of the catalyst will be affected; if the iron content is too much, the active sites of cerium will be covered, thereby reducing the redox ability of the catalyst, and sintering will occur easily during the preparation process. At the same time, excessive iron may change the selectivity of the catalyst and increase other side reactions. Therefore, the present invention limits the molar ratio of Ce element to Fe element to the above parameter range.

[0032] In some embodiments of the present invention, the molar ratio of the Ce element in the Ce oxide to the Fe element in the Fe oxide is 10:1, 10:2 or 10:3.

[0033] The present invention also provides the FeCe / SiO 2 The preparation method of the composite aerogel catalytic material comprises the following steps:

[0034] Dissolve cerium salt and iron salt in water, then add SiO 2 aerogel, after being uniformly mixed, subjecting the obtained mixed solution to a microwave hydrothermal synthesis reaction to obtain a precursor material;

[0035] Calcine the precursor material to obtain the FeCe / SiO 2 Composite aerogel catalytic materials.

[0036] In some embodiments of the present invention, the cerium salt is Ce(NO 3 ) 3 6H 2 O; the iron salt is Fe 2 (NO 3 ) 3 6H 2 O.

[0037] In some embodiments, the Ce(NO 3 ) 3 6H 2 O and SiO 2 The mass ratio of aerogel is 4.34:4.

[0038] In some embodiments of the present invention, in the microwave hydrothermal synthesis reaction, the microwave hydrothermal time is 30 min and the temperature is 250°C.

[0039] In the present invention, when the microwave time is short, the catalyst will not be sufficiently heat treated and the crystallinity will be poor, thereby reducing the catalytic activity of the catalyst; and when the microwave time is too long, the catalyst will be sintered, and its specific surface area will be reduced, which will also have a certain impact on the catalytic activity. In terms of temperature, when the temperature is too low, the reaction rate will be reduced, resulting in incomplete reaction and affecting its catalytic performance. When the temperature is too high, although the reaction rate is accelerated to a certain extent, its grain growth is too fast, which will reduce the specific surface area and the number of active sites of the catalyst. Therefore, the present invention limits the parameters of microwave hydrothermal synthesis to the above range.

[0040] In some embodiments of the present invention, after the microwave hydrothermal synthesis reaction is completed, the step of drying the obtained product is further included; the drying temperature is 80°C.

[0041] In some embodiments of the present invention, the calcination temperature is 500° C.-700° C., and the calcination time is 4 hours.

[0042] The present invention also provides the FeCe / SiO 2 Application of composite aerogel catalytic materials in catalysis of flue gas containing CO and NO.

[0043] The present invention also provides a flue gas denitration catalyst, the raw materials of which include the FeCe / SiO 2 Composite aerogel catalytic materials.

[0044] In order to better understand the present invention, the following examples are used to further illustrate the content of the present invention, but the content of the present invention is not limited to the following examples. 2 The preparation process of composite aerogel catalytic materials is as follows Figure 1 shown.

[0045] Unless otherwise specified, the raw materials and reagents used in the examples can be obtained through commercial sources.

[0046] Example 1

[0047] This embodiment provides a FeCe / SiO 2The composite aerogel catalytic material is prepared as follows:

[0048] Step 1. Accurately weigh 4.34g of cerium nitrate and 0.404g of ferric nitrate and dissolve them in 60ml of deionized water, stirring until completely dissolved. Weigh 4g of SiO 2 The aerogel carrier was added to the above solution and then placed in a microwave oven for microwave hydrothermal synthesis at 250°C for 30 minutes. The nitrate in the solution precipitated and loaded on the SiO 2 aerogel, and then put it into a forced air oven for drying at 80°C to obtain a precursor;

[0049] Step 2: The obtained precursor was calcined at 500 °C for 4 h in an inert atmosphere to decompose the nitrate into oxides to form a FeCe composite oxide catalyst, namely FeCe / SiO 2 Composite aerogel catalytic materials.

[0050] The FeCe / SiO 2 In the composite aerogel catalytic material, nCe:nFe=10:1.

[0051] Example 2

[0052] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 1, except that the calcination temperature is 600°C.

[0053] Example 3

[0054] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 1, except that the calcination temperature is 700°C.

[0055] Example 4

[0056] This embodiment provides a FeCe / SiO 2 The composite aerogel catalytic material is prepared as follows:

[0057] Step 1. Accurately weigh 4.34g of cerium nitrate and 0.809g of ferric nitrate and dissolve them in 60ml of deionized water, stirring until completely dissolved. Weigh 4g of SiO 2 The aerogel carrier was added to the above solution and then placed in a microwave oven for microwave hydrothermal synthesis at 250°C for 30 minutes. The nitrate in the solution precipitated and loaded on the SiO 2 aerogel, and then put it into a forced air oven for drying at 80°C to obtain a precursor;

[0058] Step 2: The obtained precursor was calcined at 500 °C for 4 h in an inert atmosphere to decompose the nitrate into oxides to form a FeCe composite oxide catalyst, namely FeCe / SiO 2 Composite aerogel catalytic materials.

[0059] The FeCe / SiO 2 In the composite aerogel catalytic material, nCe:nFe=10:2.

[0060] Example 5

[0061] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 4, except that the calcination temperature is 600°C.

[0062] Example 6

[0063] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 4, except that the calcination temperature is 700°C.

[0064] Example 7

[0065] This embodiment provides a FeCe / SiO 2 The composite aerogel catalytic material is prepared as follows:

[0066] Step 1. Accurately weigh 4.34 g of cerium nitrate and 1.212 g of ferric nitrate and dissolve them in 60 ml of deionized water, stirring until completely dissolved. Weigh 4 g of SiO 2 The aerogel carrier was added to the above solution and then placed in a microwave oven for microwave hydrothermal synthesis at 250°C for 30 minutes. The nitrate in the solution precipitated and loaded on the SiO 2 aerogel, and then put it into a forced air oven for drying at 80°C to obtain a precursor;

[0067] Step 2: The obtained precursor was calcined at 500 °C for 4 h in an inert atmosphere to decompose the nitrate into oxides to form a FeCe composite oxide catalyst, namely FeCe / SiO 2 Composite aerogel catalytic materials.

[0068] The FeCe / SiO 2 In the composite aerogel catalytic material, nCe:nFe=10:3.

[0069] Example 8

[0070] The FeCe / SiO 2The preparation method of the composite aerogel catalytic material is the same as that of Example 7, except that the calcination temperature is 600°C.

[0071] Example 9

[0072] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 7, except that the calcination temperature is 700°C.

[0073] FeCe / SiO prepared in test examples 1-9 2 The conversion rate of composite aerogel catalytic materials to CO and NO, the specific test method is:

[0074] The catalyst was tested for denitrification activity using a fixed bed. The experimental equipment consisted of a gas distribution box, a vertical furnace, a Fourier infrared flue gas analyzer, and a computer acquisition system. The total gas flow rate of the gas distribution box was 500 ml / min, the air velocity was 8000 h-1, and 2000 ppm CO and 500 ppm NO (carbon-nitrogen ratio was 4:1) were introduced. 2 As the balance gas. The temperature selected in the experiment is 0-800℃, and the heating rate of the vertical tube furnace is 10℃ / min. After the gas is prepared, the tube furnace is heated to the target temperature, and the NO concentration at this time is recorded, recorded as (NO)in. Then 0.5g of sample is loaded into the quartz tube, and then the quartz tube is placed in the vertical furnace. The Fourier infrared spectroscopy flue gas analyzer and the computer acquisition system are used to measure the outlet gas composition in real time. When the gas concentration reaches a stable state, the NO concentration at this time is recorded, recorded as (NO)out.

[0075] Calculate the catalyst denitrification rate:

[0076] Depend on Figure 2 It can be seen that the catalyst with an iron-cerium doping ratio of n(Ce):n(Fe)=10:2 has the best catalytic effect after being treated at 600°C (i.e., Example 5), and the NO conversion rate reaches 74% at 600°C. Under the same preparation method, as the temperature increases, the NO conversion rates of the three catalysts with different iron-cerium ratios are a process of gradually increasing first and then tending to stabilize. When the temperature rises from room temperature to 400°C, the NO conversion rate increases rapidly; when the temperature rises from 400°C to 800°C, the NO conversion rate remains basically unchanged. At high temperatures, the catalyst can no longer consume more NO, so the NO conversion rate reaches saturation and tends to stabilize.

[0077] Depend on Figure 3It can be seen that the catalyst with an iron-cerium doping ratio of n(Ce):n(Fe)=10:2 has the best catalytic effect after being treated at 600°C (i.e., Example 5), and the CO conversion rate reaches 90% at 300°C. Under the same preparation method, as the temperature increases, the CO conversion rates of the three catalysts with different iron-cerium ratios are a process of gradually increasing first and then tending to stabilize. When the temperature rises from room temperature to 200°C, the CO conversion rate increases rapidly; when the temperature rises from 400°C to 800°C, the CO conversion rate remains basically unchanged. At high temperatures, the catalyst can no longer consume more CO, so the CO conversion rate reaches saturation and tends to stabilize.

[0078] Comparative Example 1

[0079] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 1, except that the calcination temperature is 400°C.

[0080] The calcination temperature is too low, which leads to unstable pore structure of aerogel, affecting its mechanical properties and durability. Hydrophobic aerogel may become hydrophilic after heat treatment at a certain temperature. 2 The conversion rates of CO and NO by the composite aerogel catalytic material showed that the conversion rates of CO and NO were greatly reduced (the conversion rate of CO was 66% and the conversion rate of NO was 51%).

[0081] Comparative Example 2

[0082] The FeCe / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 1, except that the calcination temperature is 1000°C.

[0083] The calcination temperature is too high, which causes a significant change in the pore structure of the aerogel and changes its crystal form, thus affecting its catalytic performance, reducing its compressive strength and fracture resistance, and reducing its thermal stability, making it easy to decompose or sinter at high temperatures. 2 The conversion rates of CO and NO by the composite aerogel catalytic material showed that the conversion rates of CO and NO were greatly reduced (the conversion rate of CO was 72% and the conversion rate of NO was 46%).

[0084] Comparative Example 3

[0085] This comparative example provides a CeZr / SiO 2 The preparation method of the composite aerogel catalytic material is the same as that of Example 1, except that 0.404 g of ferric nitrate is replaced by 3.66 g of zirconium nitrate.

[0086] CeZr / SiO 2 The denitrification activity of the composite aerogel catalytic material was tested. The test method was similar to that of FeCe / SiO 2 The test method of the composite aerogel catalytic material shows that (the conversion rate of CO is 57%, and the conversion rate of NO is 63%).

[0087] Comparative Example 4

[0088] This comparative example provides a FeCe composite aerogel catalytic material, and the preparation method is as follows:

[0089] Step 1. Dissolve 0.809 g of ferric nitrate and 4.34 g of cerium nitrate in 30 mL of a mixed solution of ethanol and water in a volume ratio of 1:1, add 3 mL of glacial acetic acid and 2.25 mL of formamide, and stir magnetically to obtain a mixed solution;

[0090] Step 2. Place the obtained mixed solution in an oven at 80°C to form a gel, and soak the wet gel in anhydrous ethanol for 6 times, each time for 12 hours. After it is completely gelled and the water in the skeleton is completely replaced, place the wet gel in a reactor and perform supercritical drying to obtain a block aerogel. Place the block aerogel sample in a muffle furnace at 400°C for heat treatment for 2 hours, with a heating rate of 5°C / min, to obtain a FeCe composite aerogel catalytic material.

[0091] Comparative Example 4 uses a supercritical drying preparation method to prepare aerogel using ferrocerium as a substrate, while the present invention uses a formed industrial aerogel as a carrier to load the active elements on the carrier surface. Loading the active components on the aerogel carrier helps to disperse them more evenly, while saving costs to a certain extent, and can be used for large-scale industrial production. Its catalytic performance is improved by 5%-10% compared with that after supercritical.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A FeCe / SiO2 composite aerogel catalytic material, characterized in that: SiO2 aerogel is used as a carrier, and transition metal oxides are loaded on the carrier; the transition metal oxides are Fe oxides and Ce oxides.

2. The FeCe / SiO2 composite aerogel catalytic material according to claim 1, characterized in that: The molar ratio of the Ce element in the Ce oxide to the Fe element in the Fe oxide is 10:(1-3).

3. A method for preparing the FeCe / SiO2 composite aerogel catalytic material according to claim 1 or 2, characterized in that: The following steps are involved: The cerium salt and the iron salt are dissolved in water, and then SiO2 aerogel is added and mixed evenly, and the obtained mixed solution is subjected to microwave hydrothermal synthesis reaction to obtain a precursor material; The FeCe / SiO2 composite aerogel catalytic material is obtained by calcining the precursor material.

4. The method for preparing the FeCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: The cerium salt is Ce(NO3)3·6H2O; the iron salt is Fe2(NO3)3·6H2O.

5. The method for preparing the FeCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: In the microwave hydrothermal synthesis reaction, the microwave hydrothermal time is 30 minutes and the temperature is 250°C.

6. The method for preparing the FeCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: After the microwave hydrothermal synthesis reaction is completed, the step of drying the obtained product is also included; the drying temperature is 80°C.

7. The method for preparing the FeCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: The calcination temperature is 500° C.-700° C., and the calcination time is 4 hours.

8. Use of the FeCe / SiO2 composite aerogel catalytic material according to claim 1 or 2 in catalyzing flue gas containing CO and NO.

9. A flue gas denitration catalyst, characterized in that: The raw material includes the FeCe / SiO2 composite aerogel catalytic material as described in claim 1 or 2.

Citation Information

Patent Citations

  • CeZr composite aerogel catalytic material as well as preparation method and application thereof

    CN117718034A